Regulation of hip joint kinetics for increasing angular momentum during the initiation of a pirouette en dehors in classical ballet - Imura, A.; Iino, Y. (Human Movement Science, 2018)
This study examined how dancers regulate the hip joint kinetics to coordinate the upper and lower body angular momenta with the increased rotation of pirouette en dehors (pirouette) during the preparation. During the preparation of the pirouette, the upper body rotates greatly about the vertical axis; however, the lower extremity remains relatively stationary. Therefore, there must be specific control at the hip to coordinate the upper and lower body angular momenta in turns of increased rotation. Kinematics and kinetics of single to quadruple pirouettes performed by eight ballet dancers were analysed using a motion capture system and force plates. Peak angular momentum of the upper body around the vertical axis increased from the single to the quadruple pirouettes. The vertical components of hip abductor torque of the anterior lower limb and hip adductor and flexor torques of the posterior lower limb contributed to generating the clockwise moment acting on the upper body around the vertical axis, which was reduced by the vertical components of the hip internal and external rotator torques. Thigh flexion angles of the posterior and anterior lower limbs, respectively, at the peak adductor and abductor torques at the corresponding hip joints changed with the number of revolutions and changed the percent contribution of the relevant hip joint torques about the vertical axis. The results suggest that dancers need to regulate hip joint torques along with the thigh angles in the pirouettes depending on the number of revolutions AUTORREFERAT